2013
DOI: 10.1016/j.jmb.2013.09.028
|View full text |Cite
|
Sign up to set email alerts
|

Innate Immune Response to Arenaviral Infection: A Focus on the Highly Pathogenic New World Hemorrhagic Arenaviruses

Abstract: Arenaviruses are enveloped, negative-stranded RNA viruses that belong to the family Arenaviridae. This diverse family can be further classified into OW (Old World) and NW (New World) arenaviruses based on their antigenicity, phylogeny, and geographical distribution. Many of the NW arenaviruses are highly pathogenic viruses that cause systemic human infections characterized by hemorrhagic fever and/or neurological manifestations, constituting public health problems in their endemic regions. NW arenavirus infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 132 publications
0
21
0
Order By: Relevance
“…Robust in vitro memory CD4 + T-cell responses to LASV in antibody-seropositive surviving individuals suggested that efficient T-cell immunity develops during nonfatal infections (42). However, studies that measure the potency of T-cell responses or IFN-I levels in patients with lethal LF have not been reported (3)(4)(5)(6). We also noted that fatal vascular leakage in Cl13-infected NZB mice correlated with IFN-I-dependent platelet loss.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Robust in vitro memory CD4 + T-cell responses to LASV in antibody-seropositive surviving individuals suggested that efficient T-cell immunity develops during nonfatal infections (42). However, studies that measure the potency of T-cell responses or IFN-I levels in patients with lethal LF have not been reported (3)(4)(5)(6). We also noted that fatal vascular leakage in Cl13-infected NZB mice correlated with IFN-I-dependent platelet loss.…”
Section: Discussionmentioning
confidence: 59%
“…Studies in vitro with human cells and in vivo in nonhuman primates suggested reduced or delayed induction of type I IFNs (IFN-I), IFN-stimulated genes, and T-cell responses in fatal cases (1,(3)(4)(5)(6). However, these studies are limited by the small number of animals examined and the lack of direct comparisons between responses in patients with severe vs. mild infections.…”
mentioning
confidence: 99%
“…World arenaviruses (20). We have previously found that the L protein and NP from the Cd#1 strain of JUNV efficiently support MACV replication in a minigenome system, suggesting the feasibility of introducing viral genes from the attenuated JUNV into MACV (18).…”
Section: Figmentioning
confidence: 99%
“…Lassa hemorrhagic fever has many similar characteristics to Ebola virus disease, including the absence of interferon production and lymphoid depletion. On the molecular level, arenaviruses have been shown to suppress interferon production by targeting both upstream (i.e., RIG-I/MDA-5) and downstream signaling events (i.e., IKKε interactions, IRF-3 phosphorylation) (Koma et al, 2013). In this way each virus disrupts multiple access points in the pathways that lead to increased interferon production.…”
Section: Snipping the Alarm-wire: Preventing The Interferon Alarmmentioning
confidence: 99%